Tradisi Bedah Bumi di Jawa dalam Pandangan Islam - Khoirin Nurul Farichatin Nichlah; Ashif Az Zafi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
Indonesia has many traditions that are still very thick, one of which is in Java. In Java has a unique tradition when after eater people died, namely earth surgery. This tradition aims to pray for the deceased as well as a form of sincerity of the family left behind. This paper aims to see the tradition of earth surgery in Java and Islamic views of the tradition. The aim is to find out the tradition before the funeral takes place, the tradition after the funeral takes place and to know the Islamic view of the tradition. The research method used in writing. This is a qualitative descriptive method and a literature method. Keywords: tradition, earth surgery, Islamic outlook.